Gender differences in the kinetics and kinematics of distance running: implications for footwear design - Sinclair, J.; Greenhalgh A.; Edmundson, C. J.; Brooks, D.; Hobbs S. J. (International Journal of Sports Science and Engineering, 2012)
Interest in distance running amongst females has expanded rapidly. Although there are numerous health benefits associated with running, the occurrence of injury is well documented. Given the relative susceptibility of females to overuse running injuries, a key issue within the discipline of footwear biomechanics that has yet to be appropriately addressed is the specific demands of athletic footwear for females. The aim of this study was therefore to provide both a kinetic and 3-D kinematic comparison of male and female runners in order to determine the relative susceptibility of females to the proposed mechanisms of overuse injuries and whether based on this information, females require more specific footwear designs to meet their needs. Twelve male participants and twelve female participants` completed five successful trials running at 4.0ms-1 ± 5%. 3-D angular joint kinematics from the hip, knee and ankle were collected using an eight camera motion analysis system. In addition simultaneous tibial acceleration and ground reaction forces were obtained. Differences in impact parameters and joint kinematics were subsequently compared using independent samples t-tests. Females were found to be associated with significantly greater knee abduction, knee internal rotation and ankle eversion, whilst males were associated with significantly greater hip flexion. Based on these findings it is recommended that females select running footwear with design characteristics aimed towards the reduction of coronal plane ankle eversion in order to reduce the incidence of injury.